Relatório de Estágio na Ponto de Fuga - Martins, Helena Sofia de Magalhães (2018)
With this internship report I intend to describe the time I spent at Ponto de Fuga publishing house as an intern, from July to November 2017. I will list the various assignments I was tasked with, from proofreading to revising translations, and I will assess them critically within the context of the Editing and Publishing master’s programme. Furthermore, I will provide a brief analysis of Ponto de Fuga’s placement within the Portuguese publishing world and what kind of challenges it faces as an independent publishing house